Upaya Meningkatkan Hasil Belajar Dengan Model Pembelajaran Kooperatif Pada Materi Pembelajaran Pecahan - Marwati, Indah (Universitas Sebelas Maret, 2020)
This research is motivated by the low student achievement in the fractional material. The students' learning outcomes in the material have not been able to reach the KKM. The purpose of this research is to determine the effect of the cooperative learning model. The subjects of this study were teachers and all grade II students of SDN Tengko 01, amounting to 24 students. This research was carried out in two cycles. The instruments used were lesson plans, question sheets, lesson plans analysis sheets and APKG sheets. Data collection techniques in this study used test techniques and observation techniques. The data analysis technique used was quantitative description. The results showed that the use of cooperative learning models can be used to improve student achievement. This is evidenced by changes in abilities and an increase in the average score obtained by students after improving learning. In cycle 1 the value is 69 and in cycle 2 it becomes 82. this number can be found say that there is an increase in student learning outcomes that are quite good, seen from the results of the cycle 1 test to the final results after learning.